Delay in marriage and income inequality in Japan: The impact of the increased number of unmarried adults living with their parents on the household economy - Sawako Shirahase (Luxembourg Income Study (LIS), 2009)
The continuous decline in the fertility rate has been witnessed since 1980 in Japan. Japan's total fertility rate in 2005 is 1.32, which is far below the replacement rate, 2.08. One of the main reasons for declining the fertility rate is the delay in marriage or even shy away from marriage among young adults. In this paper, looking at youth in terms of their relation to the household, we will examine the economic disparities of unmarried adults living with their parents in Japan in comparative perspective with Europe and U.S. The countries which I analyze in this paper are France, Germany, Italy, Sweden, U.K., U.S., and Taiwan, compared with Japan. The paper consists of two parts. First, I will examine economic disparities among households with unmarried adults, and second, the determinants of co-residence with their parents will be scrutinized. The degree of the Japanese youth unemployment rate is not as high as those in European countries, but it is commonly found that the youth tend to be targeted by economic downturns, and that they are exposed to high economic risk. Young unmarried people do not always live alone, but share their households with their family, mostly their parents. Less than 20 percent of unmarried adults live alone in Japan, and in Italy and Taiwan, its corresponding figures are even lower than that in Japan. The proportion of income derived from unmarried adults in the household economy is more or less negatively associated with family income. Therefore, unmarried adults are not always dependent on their parents in the household but there are cases in which unmarried adults are the ones who support the family income by living with their parents, particularly in low-income groups. The economic role of unmarried adult children in the household differs by the level of household economy. In determining if unmarried adults live with their parents, the economic factor is important for both men and women. Since their individual income is not high enough to have their independent households, they stay in their parental home. The most interesting finding in this analysis is on the gender role in living arrangement with their parents. Unmarried female adults are less likely to stay in their parental home if their mothers are at work, while there is no significant impact of mother's work on their male counterparts. Unmarried daughters are like to be expected to take over the mother's role in the households when she is in the labor force, so there is a gendered allocation of family role for unmarried adults. Thus, the economic levels of unmarried adults and the gender constrain in allocating family roles were important in determining the living arrangement with the parents.
Keywords: 330; Income Inequality; Co-residency of unmarried adults with Parents; Delay in marriage; Einkommensverteilung; Familienökonomik; Privater Haushalt; Ehe; Japan